GC-MS Analysis and Antimicrobial Evaluation of Essential Oil from the Epicarp of Nigerian Grown Afraegle paniculata (Rutaceae) - Babatunde, Oluwatoyin; Ajayi, Grace T; O Ajayi, Ola Oluwa; Ajayi, Ibironke A (Dhaka University Journal of Pharmaceutical Sciences, 2023)
Essential oils are used as therapeutic agents in aromatherapy. In this study, the chemical composition and antimicrobial activity of the essential oils from the epicarp of Afraegle paniculata fruits from Nigeria were evaluated. The essential oil was obtained via hydro distillation and chemical components of the oils were analysed on Agilent Technologies 7890A gas chromatograph-mass spectrometry system. Antimicrobial assay was performed by disc diffusion method. GC-MS analysis revealed sixteen compounds consisting mainly of oxygenated monoterpene (39.61 %), esters (15.3 %), sesquiterpenes (13.1 %) and sesquiterpene alcohol (9.42 %). The oil showed appreciable activity against all the tested microorganisms except Aspergillus niger. At concentration of 1000 μg/ml, the inhibitory effect observed for S. aureus was 16 mm followed by 15 mm for B. subtilis and 7 mm for P. aeruginosa. The findings suggest that essential oil from A. paniculata fruits could serve as a valuable raw material for perfumery and cosmetic products. Dhaka Univ. J. Pharm. Sci. 22(1): 73-80, 2023 (June)